The Concept Of God According To Nietzsche And Syed Muhammad Naquib Al-Attas - Usmanul Khakim; M Shohibul Mujtaba; Hammada Hanifi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The purpose of this study is to examine the concept of God in the thought of Friedrich Nietzsche and Syed Muhammad Naquib al-Attas comparatively, with an emphasis on epistemological, ontological, and moral elements. To identify conceptual similarities and differences, a qualitative comparative approach was used, which included literature analysis and interpretation of the main texts of both figures. It is known that Nietzsche rejects the existence of God as a transcendent reality; he views God as a cultural construct that limits the “will to power” and produces slave morality, fostering nihilism and value relativism. Al-Attas, on the other hand, asserts that Allah is the Absolute Being, functioning as the foundation of existence and absolute morality; his concept of Tawhid is not only theological but also forms an epistemological and existential framework that integrates spiritual experience, reason, and revelation. Al-Attas's perspective distinguishes him from Nietzsche's deconstructive stance by offering a harmonious paradigm of life where divine revelation serves as the source of absolute truth and moral guidance. This outcome underscores the importance of Islamic theological foundations in addressing the chaos of meaning and values brought about by contemporary secular philosophy.